2019
DOI: 10.5539/jas.v11n5p183
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bushy Cashew (Anacardium humile A. St.-Hil.) in the State of Goiás, Brazil

Abstract: The physical and chemical characteristics of the fruits influence the consumer acceptance. The objective of this study was to perform the physical, physico-chemical and chemical characterization of fruits of accessions of bushy cashew (Anacardium humile A. St.-Hil.) (cashew nut and cashew apple) in a germplasm bank located in southwest of the state of Goiás, in Brazil, aiming at the selection of superior accessions, in order to facilitate the initiation of a program to encourage the production and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…However, these data suggest Anacardioideae is polyphyletic, retrieving Campnosperma as an early diverging lineage in Spondioideae in support of the findings of Quinn (1990, 1991) and Weeks et al (2014). Like the molecular analyses of Pell (2004) and Weeks et al (2014), this recent molecular data indicate that all tribes are polyphyletic with the exception of Dobineae (Campylopetalum and Dobinea) and Semecarpeae (including samples of Semecarpus, Drimycarpus, Nothopegia, and Melanochyla, but missing Holigarna), suggesting that the tribal classification of the family is in need of revision in order to be reflective of resolved clades (Joyce 2021;Joyce et al unpublished). At the genus level, the phylogenetic data (Joyce 2021;Joyce et al unpublished) and morphological analyses (Herrera et al 2018) also suggest that Cyrtocarpa and Poupartia are polyphyletic and confirm the findings of previous authors that Rhus is polyphyletic and in urgent need of taxonomic revision (Yi et al 2007).…”
Section: Introductionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, these data suggest Anacardioideae is polyphyletic, retrieving Campnosperma as an early diverging lineage in Spondioideae in support of the findings of Quinn (1990, 1991) and Weeks et al (2014). Like the molecular analyses of Pell (2004) and Weeks et al (2014), this recent molecular data indicate that all tribes are polyphyletic with the exception of Dobineae (Campylopetalum and Dobinea) and Semecarpeae (including samples of Semecarpus, Drimycarpus, Nothopegia, and Melanochyla, but missing Holigarna), suggesting that the tribal classification of the family is in need of revision in order to be reflective of resolved clades (Joyce 2021;Joyce et al unpublished). At the genus level, the phylogenetic data (Joyce 2021;Joyce et al unpublished) and morphological analyses (Herrera et al 2018) also suggest that Cyrtocarpa and Poupartia are polyphyletic and confirm the findings of previous authors that Rhus is polyphyletic and in urgent need of taxonomic revision (Yi et al 2007).…”
Section: Introductionsupporting
confidence: 73%
“…Terrazas (1994) proposed, but never formally named, these two clades as subfamilies Anacardioideae and Spondioideae, respectively. Pell (2004) found support for these subfamilies based on phylogenetic analysis of three plastid genes and formally circumscribed and described them. Each of Engler's tribes (sensu Mitchell and Mori 1987) was assigned to a subfamily, with Anacardieae, Dobineae, Rhoeae, and Semecarpeae grouped into Anacardioideae, and Spondiadeae ranked as Spondioideae; however, it was noted that some tribes were polyphyletic in some gene trees.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Toebe et al (2012), report that the leaf disc method was inadequate to determine the snap bean leaf area, as it was underestimated and the image analysis method was efficient because it evaluates the leaf as a whole, regardless of the weight difference between the areas. By Pearson's correlation coefficients between the features of the leaves of A. humile, it is possible to observe that width, leaf area, length and leaf weight presented significant correlation with each other (Table 2), indicating that the leaf linear measurements are directly related to the leaf area, this behavior allows to evaluate the vegetative growth, biomass accumulation and the final plant productivity (PEZZINI et al, 2018). Rev.…”
Section: Resultsmentioning
confidence: 97%
“…Besides the great potential of this fruit species due to its high vitamin C content, the leaves are also widely used in common medicine as expectorant (FERREIRA et al, 2012;PEREIRA et al, 2019;MUIANGA et al, 2016). It has been reported that these leaves have insecticidal, anti-inflammatory, antimicrobial and antioxidant properties (ANDRADE FILHO et al, 2010).…”
Section: Introductionmentioning
confidence: 99%